2008
DOI: 10.1211/ijpp.16.1.0009
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of two automated dispensing machines in UK hospital pharmacy

Abstract: Objective To assess the impact of two different automated dispensing machines (‘robots’) on safety, efficiency and staff satisfaction, in a UK hospital setting. Setting An NHS teaching hospital trust with two main sites each comprising 450 beds. A Swisslog Pack Picker automated dispensing machine was installed in the dispensary at site 1 in December 2003, and a Rowa Speedcase at site 2 in October 2005. Method A before‐and‐after study design was used on each site, with site 2 acting as a control for site 1. Sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
104
2
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(120 citation statements)
references
References 2 publications
11
104
2
3
Order By: Relevance
“…[46] This supports previous research by Fitzpatrick and colleagues [42] which reported that automation reduced the incidence of prevented dispensing incidents by 16%. However, not all medication is suitable for dispensing from an automated dispensing system and it is unclear whether items dispensed manually in the post-automation period were included in the study.…”
Section: Dispensing Errors In Hospital Pharmacysupporting
confidence: 90%
See 2 more Smart Citations
“…[46] This supports previous research by Fitzpatrick and colleagues [42] which reported that automation reduced the incidence of prevented dispensing incidents by 16%. However, not all medication is suitable for dispensing from an automated dispensing system and it is unclear whether items dispensed manually in the post-automation period were included in the study.…”
Section: Dispensing Errors In Hospital Pharmacysupporting
confidence: 90%
“…[3,[33][34][35]43,46,72] Five papers investigated the impact of automation on the types of dispensing errors. [42,[44][45][46][47] Three papers analysed prevented dispensing incidents [42,45,46] and two papers examined unprevented dispensing incidents. [44,47] Adedoye [45] reported that the most common prevented dispensing incidents associated with an automated dispensing system were labelling errors (76%, n = 81) and drug/content errors (18%, n = 20).…”
Section: Incidence In Brazilmentioning
confidence: 99%
See 1 more Smart Citation
“…The real payback period has been increased by approximately two years (six years of use, instead of four years as expected). The difference between the real ROI and the initial projected ROI for Pharmacy-based ADS improve workflow efficiency with a greater storage capacity [5,11,12]. In UK hospital pharmacies, Franklin et al [11] showed that the implementation of ADS represents a 23% increase in storage capacity in the first site and a 123% increase in the second site, compared to traditional storage [7].…”
Section: Discussionmentioning
confidence: 99%
“…[6] This increase serves to indicate the benefits of an ADS including improved safety and efficiency through reduced dispensing times, improved storage capacity and stock control, more appropriate allocation of staff to tasks with minimal time wastage and reduced dispensing errors. [7] Frequent drug stock-outs and expiry attributable to poor quantification and coordination practices [8] can also be managed using the ADS.…”
Section: Introductionmentioning
confidence: 99%